The Impact of Education Training, Principal’s Supervision on Teacher Performance in Education - GUO YONGKUN; Albattat, Ahmad; NORHIDAYAH AZMAN (International Journal of Multidisciplinary Research and Studies, 2023)
The quality of education in a country is determined by the quality of teaching, and the management of good school institutions, which suggests that principals and teachers play an important role in cultivating high-quality students. In order to ensure good teaching quality, high-quality teachers are needed. This review paper aims to summarize teacher performance from three dimensions: education training, principal supervision, and teacher competency. In this literature review, the authors use past studies to certify the relationships between education training and teachers, between principal supervision, and teacher performance. From this study, it reaches three conclusions: firstly, it can be concluded that school leaders can manage teacher quality through the supervision of classroom management, teacher qualification, and in-service training. Then, it tries to highlight the significant relationship between teachers' classroom management. Finally, it focuses on enhancing teacher quality according to quality management criteria, it is a practical and effective strategy to cultivate qualified students. This research will help the leaders realize the importance of teacher quality management and strategies that improve teacher quality, thus impacting on student performance.